PENGARUH MEDIA BONEKA TANGAN TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV SDN TAMPAR-AMPAR KECAMATAN PRAYA TENGAH TAHUN AJARAN 2020-2021 - Baiq Islami Lara Santy; I Nyoman Karna; Heri Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
Abstrack: This research aims to determine the effect of hand puppet media on the speaking skills of fourth graders at SDN Tampar-Ampar in the 2020/2021 academic year. This research is a Quasi Experimental Design type of Nonequivalent Control Group Design. The population in this study is the fourth grade students of SDN Tampar-Ampar with 44 students total. The samples in this research is 4A class as the control class and 4B as the experimental class. The sampling technique used was porposive sampling. The data collection technique in this research is an assessment rubric (pretest-posttest). Data were analyzed with the help of SPSS version 16. From the results of the study, the average pretest scores for the experimental class and the control class were 65,27 and 71,27 while the posttest scores for the experimental class and the control class were 79,82 and 73,64.. Then, the t-count value bigger than t-table at a significant level of 5% with df = 42, then Ha was accepted and Ho was rejected. The research hypothesis was accepted which reads that there is an influence of hand puppet media on the speaking skills of fourth graders at SDN Tampar-Ampar in the 2020/2021 academic year.